The Satisfaction Level of Vice Principal at Tabuk Public Schools with the Selection process of School Leaders - Al - Duran, Waleed Zamil (Journal of Educational and Psychological Sciences, 2019)
The objective of the study is Disclosure of the satisfaction level with the vice principal of public education schools about the process of selecting school leaders and identifying the most important trends in the selection process for school leaders, And compare them with the trends of the selection process prevailing in the city of Tabuk, And to determine the level of satisfaction of the vice principals of general education schools in the city of Tabuk on the process of selecting school leaders as is currently done, the researcher prepared a questionnaire consisting of (38) items In order to measure the level of satisfaction with the vice principals of public education schools in the city of Tabuk on the selection of school leaders, and distributed to the entire study community, consisting of (116) vice principals and the number of respondents (61) vice principals they were the sample of study, To answer the questions of the study and test hypotheses, The researcher had alpha-cronbach extraced, frequencies and percentages, Pearson correlation coefficient, arithmetic mean and standard deviations, and application of single-variance ANOVA analysis (F).The most important Results of the study were the average score of all the pivots which represents the level of satisfaction of the vice principals of public education schools at Tabuk, came from the selection with school leaders an average with (3.95), and a high level of satisfaction.The highest average score was "the Followed standards" with (4.15) and a high level of satisfaction, while the " Members of the Selection Committee " came last with an average (3.44) and a high level of satisfaction.Adimension "personal qualities", the highest average score with (4.32), and a very high level of satisfaction. Adimension" the candidate’s scientific qualification" it received the lowest of average score with (3.75) and a very high level of satisfaction.The highest average score of Phrases it was "peace of thought and methodology"with (4.64), and a very high level of satisfaction. and the lowest average score of Phrases was "passing the school leadership test conducted by the National Center for Measurement and Evaluation by not less than 52%" with an average (3.08), and medium level of satisfaction.There were no statistically significant differences in the level of satisfaction of the vice principals of public education schools in Tabuk about the selection with school leaders according to the variables (stage, number of training courses, and experience), The most important recommendations to involve the educational administrations in the regions with the process & standards setting, expand the base of Selection Committee , By giving more participation to non-governmental educational institutions and bodies with the selection process, achieve cooperation between Department of Management and Educational Planning at Tabuk University (DMEPTU)And school leadership Department at Tabuk Region, in the field of setting standards, Scientific selection, and the DMEPTU contribution with the process, rehabilitation and training of school leaders.